2013
DOI: 10.1001/jamapediatrics.2013.502
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Cohort Study of Undervaccination in 8 Managed Care Organizations Across the United States

Abstract: OBJECTIVES To examine patterns and trends of undervaccination in children aged 2 to 24 months and to compare health care utilization rates between undervaccinated and age-appropriately vaccinated children. DESIGN Retrospective matched cohort study. SETTING Eight managed care organizations of the Vaccine Safety Datalink. PARTICIPANTS Children born between 2004 and 2008. MAIN EXPOSURE Immunization records were used to calculate the average number of days undervaccinated. Two matched cohorts were created: 1 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 29 publications
2
127
1
5
Order By: Relevance
“…Contrary to the rising trend in the US, 13,14 this analysis also suggested that undervaccination in Taiwan decreased over time. The decreasing prevalence and magnitude of undervaccination against pertussis highlighted public health successes in improving access to healthcare, vaccine delivery, and systems to identify and catch up children behind on immunizations over the past decade.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Contrary to the rising trend in the US, 13,14 this analysis also suggested that undervaccination in Taiwan decreased over time. The decreasing prevalence and magnitude of undervaccination against pertussis highlighted public health successes in improving access to healthcare, vaccine delivery, and systems to identify and catch up children behind on immunizations over the past decade.…”
Section: Discussioncontrasting
confidence: 59%
“…Second, prior studies estimate that overall 10%-25% of children were undervaccinated because of vaccine-hesitant parents. 13,16,17 Our study, however, was unable to provide reasons for undervaccination as this information was not captured in the NIIS or assessed through reviews of medical records. Third, pertussis is highly underreported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Иммунизация является одним из наиболее значимых достижений обществен-ного здравоохранения за последнее столетие [1]. Однако в последнее время серьез-ную обеспокоенность среди научного сообщества вызывает снижение уровня вак-цинации в мире, обусловленное не недостатком ресурсов, а осознанным отказом от вакцинации [см., например : 2, 3].…”
Section: Introductionunclassified